2006
DOI: 10.1021/ie051457q
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Arsenic on Layered Double Hydroxides:  Effect of the Particle Size

Abstract: This paper describes a study of arsenic(V) adsorption on appropriately conditioned calcined layered double hydroxide (LDH) adsorbents. Conditioning the adsorbent significantly reduced the dissolution previously observed with uncalcined and calcined LDH. The adsorption rates and isotherms have been investigated in batch experiments. As(V) adsorption is shown to follow a Sips-type adsorption isotherm. The As(V) adsorption rate on conditioned LDH increases with decreasing adsorbent particle size; the adsorption c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 22 publications
10
99
0
1
Order By: Relevance
“…Those pollutants include: oxyanions [70][71][72][73][74][75], monoatomic anions [76][77][78] cations [79][80][81], organics [82][83][84], and gas [85,86]. For example, Kovanda et al [87] demonstrated the capabilities of Co:Mn:Al LDH (calcined at 500°C) in the total oxidation of ethanol (Figure 4).…”
Section: Heave Metal Capture In Liquid Wastementioning
confidence: 99%
“…Those pollutants include: oxyanions [70][71][72][73][74][75], monoatomic anions [76][77][78] cations [79][80][81], organics [82][83][84], and gas [85,86]. For example, Kovanda et al [87] demonstrated the capabilities of Co:Mn:Al LDH (calcined at 500°C) in the total oxidation of ethanol (Figure 4).…”
Section: Heave Metal Capture In Liquid Wastementioning
confidence: 99%
“…At equilibrium, the adsorption equilibrium isotherm can be represented by the Sips model (Equation (3)), which was previously reported to describe the arsenic adsorption process in batch and continuous adsorption (Dadwhal et al, 2009;Yang et al 2006). There are numerous other adsorption equilibrium models, e.g.…”
Section: Theory and Calculationmentioning
confidence: 99%
“…Assuming homogeneous spherical adsorbent particles, a concentration-independent diffusivity (this assumption was relaxed by Yang et al (2006) without offering any particular advantage in the model fit), the intra-particle transport and solute uptake is described by the following equation (Yang et al, 2006):…”
Section: Homogenous Surface Diffusion Modelmentioning
confidence: 99%
“…Anions contribute to the thermodynamic stability of the LDH by affecting both enthalpy and entropy [10]. For a given pair of metal ions, the affinity of the LDH for different anions varies in the order CO ions by a mineral acid (HCl or HNO 3 ) at pH 4.5 [14] and (b) calcination of the pristine LDH to yield a defect oxide phase and subsequent reconstruction of the LDH by soaking the oxide residue in As(V) solution [15]. The uptake by the former method is essentially through anion exchange at a pH close to the dissolution pH of the LDH, while the latter is based on the memory-effect of LDHs.…”
Section: Introductionmentioning
confidence: 99%